EVALUATION OF ANTITUMOR ACTIVITY OF GLUTAMINASE FREE L-ASPARAGINASE FROM INDIGENOUS BACTERIAL STRAINS FOR POTENTIAL CHEMOTHERAPEUTIC APPLICATION - ANJANA SHARMA; ISLAM HUSAIN; SHUBHI MISHRA (International Journal of Pharma and Bio Sciences, 2014)
A total of 154, bacterial strains were isolated from rhizospheric soil, river water and were screened for L-asparaginase activity, out of which 54 bacterial strains were found to be L-asparaginase positive strains. These L-asparaginase positive strains (54) were further screened for their glutaminase activity. Among them six bacterial strains exhibiting glutaminase free L-asparaginase activity were selected and identified as Pseudomonas otitidis, Ochrobactrum anthropi, Paenibacillus lactis, Enterobacter cloacae, Bacillus subtilis and Escherichia fergusonii on the basis of morphological, cultural, biochemical characteristics and 16S rRNA gene sequencing. L-asparaginases from these bacterial strains were evaluated for their antitumor activity against breast cancer (T47D, MDAMB-231) and T-lymphoblast acute lymphoblastic leukemia (MOLT-4) cell lines and also for their in vitro serum and trypsine digestion half-life. Extracellular L-asparaginase from P. otitidis showed maximum 82.5±0.02% and 28.84±0.02% growth inhibition towards T47D and MDA-MB-231 cells, respectively and 37 h and 30 min in vitro serum and trypsin half life respectively. These results demonstrated that P. otitidis L-asparaginase possess effective antitumor activity, prolonged in vitro serum and trypsin digestion halflife as compared to previous reports. Thus, glutaminase free L-asparaginase from P. otitidis can be further explored for improving L-asparaginase therapy and other biotechnological applications.